HUMAN DIMENSION OF START-UP - Š. Slávik; P. Srovnalíková; V. Navickas; Т. Girchenko (Фінансово-кредитна діяльність: проблеми теорії та практики, 2020)
Abstract. Start-up is a young and very small enterprise which staffing and human relationships are different from the internal environment of larger enterprises. Research has therefore focused on founders/leaders of start-ups and relationships inside start-up teams. The result of the research is the basic personal characteristics of the leading people (age, education, reasons for entering the business and others), the quality of their leadership and the quality of teamwork. Since a start-up is developing vigorously, leadership and teamsmanship are monitored on the base of business idea development and investment cycle. Start-up founders are better leaders than managers, teams are better at handling extraordinary situations than standard operation, quality of leadership is situationally conditioned to a certain extent by start-up development phase. Start-ups contain contradictions with significant asymmetry, which are the expression of their limited strengths and considerable weaknesses. The lack of living and work experiences is substituted by the enthusiasm, the diligence and the sense of teamwork that have their limits, and therefore the solution is to professionalize the start-up in in the later stages of its development.